Grief and the shaping of Muslim communities in north India, c. 1857-1940s - Tignol, Eve 1986- (Cambridge, UK; New York, USA: Cambridge University Press, 2023)
"This book contributes to significant on-going discussions on nationalism, collective emotions and memory in modern print cultures. It highlights how emotions were collectively cultivated and debated for the shaping of Muslim community identity and for political mobilisation in colonial India after the 1857 Uprising"--
List of figures -- Acknowledgments -- Note on transliteration -- List of abbreviations -- Introduction -- A garden lost: grief and pain in 1857 shahr āshob poetry -- Useful grief: the Aligarh movement -- Memorials, feelings, and public recognition, c. 1911-1915 -- Empowering grief: poetry and anti-colonial sentiments in the early twentieth century -- Nostalgia in Delhi: local memory and identity, c. 1910-1940 -- Epilogue -- Glossary -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: Muslims -- India, North -- Social conditions; Sociology; Muslims -- India, North -- Ethnic identity; Collective memory -- India, North; Emotions -- Political aspects -- India, North; India, North -- Politics and government; India -- History -- Sepoy Rebellion, 1857-1858.